2015
DOI: 10.14202/vetworld.2015.461-466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of species, breed, and age on bacterial load in bovine and bubaline semen

Abstract: Aim:The present study was conducted to investigate the effect of species, breed and age on bacterial load in fresh and frozen semen of Cattle and Buffalo bull.Materials and Methods:Present study covered 56 cow and 10 buffalo bulls stationed at Central Semen Station Anjora, Durg (Chhattisgarh). Impact of breeds on bacterial load in semen was assessed using six breeds of cattle viz. Sahiwal, Gir, Red Sindhi, Tharparkar, Jersey and Holstein Friesian (HF) cross. Cow bulls were categorized into four different group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
2
13
2
1
Order By: Relevance
“…In other species, Staphylococcus epidermidis in boar semen [43] and CoNS in human semen samples [45] were identified. e discrepancy found in the present study when compared to the above authors may be due to differences in sample size, bacteriological techniques [24], and age and breeds of animals [17].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In other species, Staphylococcus epidermidis in boar semen [43] and CoNS in human semen samples [45] were identified. e discrepancy found in the present study when compared to the above authors may be due to differences in sample size, bacteriological techniques [24], and age and breeds of animals [17].…”
Section: Discussioncontrasting
confidence: 93%
“…On the contrary, a lower prevalence comparable to current results, 33.2% [44] and 35.3% [45], was reported in human semen samples. is difference in bacterial contamination of semen may be due to differences in species, age, breed, season [17,46], anatomy, physiology, and management [41]. It may also be ascribed to unsanitary conditions during semen collection, transportation, and processing or resistance to antibiotics used in semen extender [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly Bousseau et al (1998) reported that two extenders containing animal products (Triladyl) and egg yolk plus milkbased extender (Laciphos) showed moderate (10 to 60 CFU/ ml) contamination with bacteria or mycoplasma while no contamination in Biociphos® lecithin containing diluents. In contrary to present findings, Sannat et al (2015) reported higher bacterial load in frozen semen of cattle and buffalo bulls in conventional egg yolk based extender as compared to present values of microbial load in conventional egg yolk based extender in HF cross (1.10×10 3 ), Sahiwal (9.61×10 2 ), Gir (1.09×10 3 ), Red Sindhi (6.56×10 2 ), Jersey (1.92×10 3 ) and Tharparkar (6.11×10 2 ) bull. In comparison to present findings higher values of bacterial load was reported by Wierzbowski et al (1984) in crossbred cattle bull (1.1×10 3 CFU/ml) and Patel et al (2011) in different crossbred CB-576 (1.26×10 3 CFU/ml), CB-581 (3.49×10 3 CFU/ml), CB-585B (5.9×10 3 CFU/ml), CB-594 (1.1×10 3 CFU/ml) and pure Holstein Friesian (HF-439) bull (5.38×10 3 CFU/ml).…”
Section: Resultscontrasting
confidence: 99%
“…Recently, bacterial organisms such as Micrococcus luteus, Pseudomonas aeruginosa, S. epidermidis and Staphylococcus intermedius have been detected in frozen bovine semen (Abro et al, 2016). Sannat et al (2015) described bacterial loads found in fresh and frozen semen from different breeds of cattle and buffalo. In Iranian bovine and buffalo semen, Dehkordi et al (2014) identified Brucella abortus and Brucella melitensis, which are highly contagious zoonotic pathogens of humans and the leading pathogenic bacterial causes of abortion in ruminants.…”
Section: Introductionmentioning
confidence: 99%